2020
DOI: 10.1101/2020.07.08.192328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expansion Microscopy provides new insights into the cytoskeleton of malaria parasites including the conservation of a conoid

Abstract: AbstractMalaria is caused by unicellular Plasmodium parasites. Plasmodium relies on diverse microtubule cytoskeletal structures for its reproduction, multiplication or dissemination. Due to the small size of this parasite, its cytoskeleton has been primarily observable by electron microscopy. Here, we demonstrate that the nanoscale cytoskeleton organization is within reach using ultrastructure expansion microscopy (U-ExM). I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…This presence of tubulin in a Plasmodium conoid complex provides additional support to our data showing the conservation of numerous conoid-associated proteins in all Plasmodium zoite forms. We have previously shown that SAS6L and Myosin B locate to an apical ring in Plasmodium also [42,63], and these co-locate with the tubulin ring in Plasmodium ookinetes [62].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This presence of tubulin in a Plasmodium conoid complex provides additional support to our data showing the conservation of numerous conoid-associated proteins in all Plasmodium zoite forms. We have previously shown that SAS6L and Myosin B locate to an apical ring in Plasmodium also [42,63], and these co-locate with the tubulin ring in Plasmodium ookinetes [62].…”
Section: Discussionmentioning
confidence: 88%
“…With any further reduction in the tubulin component in Plasmodium spp., or other Aconoidasida, detection of conoid tubulin by ultrastructural approaches would be even more challenged. However, the very recent application of ultrastructure expansion microscopy (U-ExM), in combination with anti-tubulin staining, has revealed that a ring of tubulin is present in P. berghei ookinetes at the very apex of the cell, beyond the apical termini of the subpellicular microtubules at APR2 [62]. This position is consistent with the location of the three conoidal rings we observe by TEM (Fig 8B-D) and the thicker posterior conoidal ring is the most likely location of this tubulin given its presence here in Haemoproteus and Leucocytozoon.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that this curious polarity must offer some advantage over a uniform distribution of microtubules [64]. The polar rings are arranged perpendicularly to the microtubules in T. gondii tachyzoites and Plasmodium ookinetes, yet are tilted towards the ventral side in sporozoites [64,69] (Figure 1B). This could direct secretion of microneme-based adhesins specifically to the ventral side, allowing a better maintenance of substrate contact and hence more persistent gliding.…”
Section: Marshalling Motility and Enveloping Entrymentioning
confidence: 99%
“…One of the stumbling blocks in understanding the roles of the alveolins was imaging the small, densely packed structures. However recent advances in expansion microscopy has allowed unprecedented localization of individual alveolins and microtubules in the cell [69,72,89]. Determining their precise localization will allow functions for individual proteins to be suggested, informing future research.…”
Section: Stress-resistant Scaffoldingmentioning
confidence: 99%
“…The round zygotes undergo huge and rapid morphological changes, gaining a protrusion, elongating and maturing to finally form an elongated, crescent-shaped ookinete ( Guttery et al., 2015 ; Bennink et al., 2016 ). The ookinete’s apical rings are formed at the same time and organize the SPM of > 40 microtubules ( Bertiaux et al., 2020 ) under the IMC. These are initially seen at the apical protrusion of the zygote but extend during zygote elongation into a “dome-like” structure under the IMC ( Wang et al., 2020 ).…”
Section: Inner Membrane Complex Structure and Function Throughout Thementioning
confidence: 99%